2016
DOI: 10.1088/0957-4484/27/18/185701
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of the combined effects of sulfur vacancies and analyte adsorption on the electronic properties of single-layer MoS2

Abstract: We report a first-principles theoretical investigation on the electronic structure and electron transport of defective single-layer (SL) MoS2, as well as of corresponding structures adsorbed with benzyl viologen (BV), which was shown to provide improved performance of a field effect transistor. O2 adsorption was included to gain an understanding of the response upon air-exposure. Following analysis of the structure and stability of sulfur single vacancy and line defects in SL MoS2, we investigated the local tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 78 publications
5
38
1
Order By: Relevance
“…Meanwhile, the density of states (DOS) showed that it has a half‐metal behavior and obtained the whole spin polarization (Figure d,e). Furthermore, Akdim et al reported that when the O 2 molecule is adsorbed at vacancy‐defected MoS 2 , the impurity states emerge at the bandgap (Figure f) . Meanwhile, the impurity states lead to a decrease of the transport properties of the system (Figure g).…”
Section: D Doped Transition‐metal Dichalcogenidementioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the density of states (DOS) showed that it has a half‐metal behavior and obtained the whole spin polarization (Figure d,e). Furthermore, Akdim et al reported that when the O 2 molecule is adsorbed at vacancy‐defected MoS 2 , the impurity states emerge at the bandgap (Figure f) . Meanwhile, the impurity states lead to a decrease of the transport properties of the system (Figure g).…”
Section: D Doped Transition‐metal Dichalcogenidementioning
confidence: 99%
“…g) I – V characteristics when the tip is positioned on S in pristine single‐layer (SL) MoS 2 , on a sulfur vacancy (SV), and on oxygen for the corresponding SV+O 2 adsorbed structure. f,g) Reproduced with permission . Copyright 2016, IOP Publishing Ltd.…”
Section: D Doped Transition‐metal Dichalcogenidementioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Very recently, different groups have analyzed the interactions of some molecules in a defective MoS 2 monolayer. [27][28][29][30][31][32] The first two works show both experimentally and theoretically the molecular chemisorption or dissociation for O 2 molecules on MoS 2 defects. Li et al extended the study to other molecules on a S vacancy, 29 while Sahoo and coworkers applied a similar analysis for an antisite, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Two good examples are the oxidation of the MoS 2 borders [28] and the sulfur vacancy self-healing using thiol molecules [29]. Even the molecular dissociation of O 2 molecules over MoS 2 defects has been shown very recently, both experimentally and theoretically [31,32].…”
Section: Introductionmentioning
confidence: 99%